Development and performance evaluation of a water lifting device - MANDAL, SUBRATA KUMAR; KUMAR, B SAMPATH (The Indian Journal of Agricultural Sciences, 2023)
The uninterrupted availability and price of electric power is a great solicitude for a common man; thus, irregular power availability for irrigation is a daily problem faced by rural farmers. In most rural communities, hand-operated water pumps are very predominant due to lack of electricity to power borehole water systems. Conventional energy is also a great concern and now, core attention of the people is being diverted towards the use of an alternate form of energy derived from human and animals. The need for water as a basic necessity in life has led to various developmental and engineering innovations that are designed to meet this need optimally. The water pump is the most useful machine, and it is the second most commonly used equipment by the farmers for irrigation purposes. An appropriate alternative to diesel pump, which requires neither diesel nor electricity, yet meets irrigation requirements, may be beneficial. With this, a simple hand-operated water-lifting device has been developed at CSIR-Central Mechanical Engineering Research Institute at Durgapur, West Bengal. Three prototypes were developed and evaluated successfully. From the results, it has been observed that, input effort has the largest effect on efficiency. The highest efficiency was found as 80% in case of prototype-III.